School-centred leadership : putting educational policy into practice (South Melbourne : Nelson, 1993)
Organisation and policy development. Policy leadership in Australia. International case studies.
Keywords: Education; School management; Education and state; School management and organization -- Decision making; School management and organization -- Decision making -- Case studies; Educational leadership; Educational leadership -- Case studies; Education and state -- Case studies